Diseño, desarrollo e implementación de un Sistema de Control de Asistencia para los docentes de la carrera de Ingeniería de Sistemas de la Universidad Politécnica Salesiana Sede Quito - Chiriboga Almendariz, Carlos Gabriel (2017)
Having a way to control the attendance of staff regarding their work activities has always been an indispensable requirement for any company or institution. Such a record allows us to have a general idea of the performance carried out by each of the individual employees, as well as of the group in general, and it enables decision-making related to the information obtained from the records. Currently, the study program of Systems Engineering does not have a mechanism that allows for the management and control of the attendance of teachers at the campus. The records are kept in biometric systems, located in different places on the campus. In case monthly reports are needed of the teachers, they are generated manually, with the consequent complications that are generated by this kind of record. The objective of the project was to design an application that would make it possible to keep records and to manage the attendance of teachers on the campus where they work, presenting statistics and reports in a significantly faster and more efficient way.